Analysis of Antimicrobial and Antioxidant Activities of Chenopodium ambrosioides: An Ethnomedicinal Plant - Muhammad Ajaib; Tanveer Hussain; Saleha Farooq; Mehrban Ashiq (Journal of Chemistry)
The antimicrobial and antioxidant potential of Chenopodium ambrosioides L. was explored. Antimicrobial potential was investigated through zone of inhibition and minimum inhibition concentration whereas antioxidant potential of selected plant was evaluated through different techniques, that is, total phenolic contents, total flavonoids content, DPPH assay, ABTS assay, and metal chelating. It is concluded that both parts showed good to satisfactory antimicrobial and antioxidant results. The maximum antibacterial potential is exhibited by bark macerated in petroleum ether against Bacillus subtilis (33±1.5 mm) and maximum antifungal potential exhibited by methanol extracts of fruit against Aspergillus niger (16±1.5 mm). Aqueous extracts failed to show any activity against selected organisms. The minimum (significant) MIC value exhibited by fruit extract against Staphylococcus aureus was 0.009±0.02 at 0.7 mg/mL. Aqueous extracts of bark and fruit exhibited maximum antioxidant potential in all assays except DPPH assay. Petroleum ether bark extract showed maximum % DPPH value.